Distribution and characteristics of rearranged hopanes in the black shale of the Chang 9 member, the Upper Triassic Yanchang Formation in the Ansai area, Ordos Basin, North China - Han Yue; Yan Liu; Rongxi Li; Xuefeng Liu (PLoS ONE, 2025)
Shale samples from source rocks of the Upper Triassic Yanchang Formation (Chang 9 member) in the Ansai area, Ordos Basin, North China, were analyzed using gas chromatography – mass spectrometry (GC-MS) to investigate the distribution, abundance, and enrichment mechanisms of rearranged hopanes. Four rearranged hopane series were detected, with all four present simultaneously in individual samples. Analysis of the C₃₀ hopane series (regular C₃₀H, diahopane C₃₀D, and neohopane C₃₀E) using a ternary diagram revealed a distinct linear trend, demonstrating a systematic, inverse relationship between the abundance of regular hopane and the combined abundance of its rearranged counterparts. These results provide strong evidence that C₃₀D and C₃₀E in the Chang 9 shales are diagenetic products derived from C₃₀H, sharing a common biological precursor. Both diasteranes and regular steranes with the ββ configuration were correlated positively in abundance with rearranged hopanes, further supporting a common origin linked to specific organism assemblages rather than widespread organisms. Samples deposited under highly saline, suboxic sedimentary environments displayed relatively high abundances of rearranged hopanes, indicating the critical role of depositional conditions in their enrichment. Multi-proxy analysis revealed a complex, non-linear control of thermal maturity on rearranged hopane abundance. The C₃₀ Rearranged Hopane Index showed statistically significant positive correlations with multiple maturity parameters (including sterane and hopane isomerization ratios), indicating maturity as a primary driver in the early oil window. However, this trend diverged at higher maturity levels, suggesting that other factors, such as the catalytic activity of the mineral matrix, become dominant. Our findings establish a robust biomarker-based framework for interpreting oil-source correlations and informing petroleum exploration in the Ordos Basin, particularly for the Chang 9 member source rocks.